2022
DOI: 10.1259/dmfr.20210140
|View full text |Cite
|
Sign up to set email alerts
|

Can gray values be converted to Hounsfield units? A systematic review

Abstract: Objectives: The purpose of this systematic review was to answer the focus question: “Could the gray values (GVs) from CBCT (cone beam computed tomography) be converted to Hounsfield units (HUs) in multidetector computed tomography (MDCT)?” Methods: The included studies try to answer the research question according to the PICO strategy. Studies were gathered by searching several electronic databases and partial grey literature up to January 2021 without language or time restrictions. The methodological assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…On the contrary, the latest systemic review, published in 2022, reported that greyscale values from CBCT could not be converted into HUs. The article reported that three conversion steps (Equipment calibration, correlation, prediction equation models, and standard formula) are needed to obtain the CBCT‐HUs 35 . Since the bone density of the present study was obtained from the gray scale values acquired directly from the software, this is a clear limitation and potential source of bias in this study.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the latest systemic review, published in 2022, reported that greyscale values from CBCT could not be converted into HUs. The article reported that three conversion steps (Equipment calibration, correlation, prediction equation models, and standard formula) are needed to obtain the CBCT‐HUs 35 . Since the bone density of the present study was obtained from the gray scale values acquired directly from the software, this is a clear limitation and potential source of bias in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It was proved that the mineral density of the osseous tissue reflects the biological activity of the bone; thus, attempts are being made to assess bone density using such a simple examination as CBCT [47]. Nevertheless, it is proven that CBCT equipment calibration and further conversion steps are needed to reliably assess the bone density in CBCT imaging [48]. Due to the fact that the imaging was performed at a remote facility, this was impossible, which constitutes a limitation of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Detectors receive the signal and convert it into electrical pulses sent and analyzed by a computer. As a result, data obtained with the scanning process contain cross-sectional images of the human body [164,165]. Modern CT systems develop several special techniques.…”
Section: Computed Tomographymentioning
confidence: 99%